2021
DOI: 10.4314/ahs.v21i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative yield of different active TB case finding interventions in a large urban TB project in central Uganda: a descriptive study

Abstract: Introduction: Systematic screening for TB among patients presenting to care and among high risk populations is recom- mended to improve TB case finding. We aimed to describe the comparative yield of three TB screening approaches imple- mented by a large urban TB project in central Uganda. Methods: We abstracted data on the screening cascade from 65 health facilities and their surrounding communities (num- bers screened, with presumptive TB, receiving a diagnostic test and diagnosed with TB) from the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…In addition, the result from this study reported a higher NNS of 5402 ((95% CI: 5347–6526) in Maternal Child Health (MCH). The findings are consistent with a similar study conducted in Kampala that reported a higher NNS of 8410 in the MCH [ 42 ]. Higher NNS in MCH could point to the quality of TB screening, which calls for implementers and managers in MCH to strengthen screening quality in this area.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the result from this study reported a higher NNS of 5402 ((95% CI: 5347–6526) in Maternal Child Health (MCH). The findings are consistent with a similar study conducted in Kampala that reported a higher NNS of 8410 in the MCH [ 42 ]. Higher NNS in MCH could point to the quality of TB screening, which calls for implementers and managers in MCH to strengthen screening quality in this area.…”
Section: Discussionsupporting
confidence: 93%
“…The screening yield was different among females and males in both HCI at 5.5% (55/1000) in females, and males, 6.0% (60/1000) P <0.01, and in PCF at 0.28 (280/100000) in females and males at 1.12 (1200/100000) P <0.01. The higher screening yield among men in both strategies is consistent with findings from several TB prevalence surveys and studies that report a higher prevalence of TB among men [ 42 , 43 ]. It could be because men are sometimes more exposed to predisposed factors like alcohol and smoking.…”
Section: Discussionsupporting
confidence: 87%
“…One intervention for TB-HIV co-infection found that community-based TB screening increased screening efforts but decreased presumed TB and TB positive cases identified. 45…”
Section: Resultsmentioning
confidence: 99%
“…One intervention for TB-HIV co-infection found that community-based TB screening increased screening efforts but decreased presumed TB and TB positive cases identified. 45 There were a total of 39 community service interventions focused on HIV testing -17 interventions distributed HIVST to men (primary or secondary distribution), [46][47][48][49][50][51][52][53][54][55][56][57][58] 15 provided community/workforce testing (non-HIVST), 52,53,55,[59][60][61][62][63][64][65][66][67][68][69][70][71] and 11 provided home-based HIV testing services. 46,54,61,69,[72][73][74][75] Community services outperformed standard of care facility services 48,52,60,61,65,67,72,73 and mobile and targeted venue testing such as work were more cost...…”
Section: Community Servicesmentioning
confidence: 99%
“…The first TB paper is by Laura Madukaji and colleagues from Nigeria. They report on “Early detection of Pre-XDR TB with line probe assay in a high TB burden country.” 1 This is followed by a paper from Uganda, in which Andrew Kazibwe and colleagues report on “the yield of different active TB case finding interventions in a large urban TB project, in central Uganda.” 2 . They describe the comparative yield of three active case finding interventions: “health facility-based screening, targeted community screening; and household contact tracing.” They discuss the merits and demerits of the different approaches.…”
mentioning
confidence: 99%